Univoscism and Monadology in Post-Avicennan Iranian Philosophy (Sadrâ al-Shîrâzii 's Ishrâqî Hermeneutics of Ibn al-`Arabî 's Gnosis and His Dicussion of Avecennan Ontology) - Segovia, Carlo A. (ENDOXA, 2002)
«One» and «Many» have been many times studied both from a theologícal and from an ontological viewpoint. In the realm of Eastem Islamic Phibsophy and in the background of its Neoplatonic basical directives. Sadrâ al-Shîrâzii (ob. 1640) develops an ontological analysis of this traditional topic which differs from the one formerly displayed by Muslim Peripatetics. By adopting and continuing Ibn al-`Arabî 's gnosis and al-Suhrawardî's Oriental wisdom he discusses Avicenna's distinction between a Necessary Being and a multiplicity of possibe beings, as well as Avicenna's tendency to consider existence as accidental. Based upon the coimplication of three main concepts: isâlat al-wujûd (priority of being), wa dat al-wujûd (unity of being) and tashkîk (intensive differentiation of being), Sadrà's monadological univocism, and in general Post-Avicennan Iranian philosophy may help us to revaluate some philosophical issues which nowadays attemp to appear in a new ligh.